2008
DOI: 10.1093/beheco/arn035
|View full text |Cite
|
Sign up to set email alerts
|

Sex, melanic coloration, and sibling competition during the postfledging dependence period

Abstract: Success in sibling competition is one of the main factors determining individual body condition in the early stages of life and consequently offspring survival and fitness. In birds, most studies on this topic have been focused on the nesting period, but sibling competition still continues during the postfledging period. We studied sibling competition over 3 years during the postfledgling dependence period in the Eurasian kestrel Falco tinnunculus, a reversed sexually size dimorphic species. Contrary to that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
(60 reference statements)
2
43
0
1
Order By: Relevance
“…The condition dependence of melanin-based traits in nestlings can be a by-product of sexual selection exerted on adult males or, alternatively, the outcome of selection on yearlings to express colour traits that signal dominance (Vergara and Fargallo 2008). However, the sub-terminal black bands on the tail feathers in young kestrels are retained for a year after fledging, and both males and females can breed in this time lapse (Village 1990).…”
Section: Condition-dependent Expression Of Black Tail Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition dependence of melanin-based traits in nestlings can be a by-product of sexual selection exerted on adult males or, alternatively, the outcome of selection on yearlings to express colour traits that signal dominance (Vergara and Fargallo 2008). However, the sub-terminal black bands on the tail feathers in young kestrels are retained for a year after fledging, and both males and females can breed in this time lapse (Village 1990).…”
Section: Condition-dependent Expression Of Black Tail Bandsmentioning
confidence: 99%
“…Furthermore, within breeding adults, these traits were differentially associated with body mass and laying date. Thus, in the kestrel, melanin-based traits can be considered as indexes of quality (Vergara and Fargallo 2008;Vergara et al 2009Vergara et al , 2010 and it would of interest to examine whether eumelanin-and pheomelanin-based colour traits are differentially costly to produce. If evidence for condition-dependent expression of melanin-based coloration in the kestrel is accumulating, little is known about the extent to which coloration is genetically inherited.…”
Section: Condition-dependent Expression Of Black Tail Bandsmentioning
confidence: 99%
“…Previous studies suggest that the expression of melaninbased coloration in kestrels is associated with indicators of body condition, mate choice and environmental conditions (Fargallo et al, 2007a,b;Vergara and Fargallo, 2008;Vergara et al, 2009;Parejo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nestling kestrels might attain more benefits through larger body fledging sizes than by bearing highly coloured plumage at the back. However, Vergara et al have shown that, during the post-fledging dependence period, males showing a higher proportion of grey in the rump captured larger prey than browner males (Vergara and Fargallo, 2008), which could indicate that rump colouration in male kestrel nestlings could act as an intraage class indicator of dominance and, hence, that at least plumage colouration of some body parts may also confer benefits to nestlings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fargallo et al (Fargallo et al 2007a;Fargallo et al 2007b) have shown experimentally that the size of the grey patch on the rump of male nestlings just before fledging increases in good environmental conditions (Fargallo et al, 2007a) and decreases with increased concentrations of plasma testosterone (Fargallo et al, 2007b). Also, male fledglings with a larger grey area on the rump have been shown to be more efficient hunters (Vergara and Fargallo, 2008), which suggests that rump colouration could function as an intra-age class indicator of dominance (Senar, 2006). Altogether, these pieces of evidence would suggest that melanin plumage colouration of the rump and, to a lesser extent, the back may function as indicators of phenotypic quality in adult males and young kestrels.…”
Section: Introductionmentioning
confidence: 99%